Knowledge, Attitude and Practice of Breast Self Examination in Female Health Workers in Olabisi Onabanjo University Teaching Hospital, Sagamu, Nigeria - AOJ, Agboola; AM, Deji-Agboola; KS, Oritogun; AA, Musa; TY, Oyebadejo; BA, Ayoade (IIUM Medical Journal Malaysia, 2009)
Background: Breast cancer is the leading cause of cancer mortality in women worldwide. This study was designed to assess the knowledge, attitude and practice of breast self examination (BSE) among female health workers in Sagamu. Methods: Questionnaire was used to obtain information such as demographic characteristics, knowledge of breast cancer, attitudes towards BSE and questions relating to practices of BSE from female health workers. Statistical analysis was carried out using descriptive statistics and Chi Square method. Results: The medical doctors had more knowledge about breast cancer than the nurses and laboratory scientists. The medical doctors (81.8%), laboratory scientists (56.5%) and the nurses (41.4%) knew the correct timing and frequency for performance of BSE. The monthly practice of BSE was very low among the nurses (30%), while only 68.2% of the doctors and 78.3% of laboratory scientist admitted carrying out BSE monthly. The doctors (68.2%), nurses (35.7%) and laboratory scientist (30.4%) started BSE below the age of 19 years. Conclusion: The results indicate that the nurses had poor attitude towards BSE and this affected their practice of BSE though they had knowledge. The finding that some of the female health workers did not practice BSE, suggests that there is a need for continuing education programs to change attitude and behaviour towards BSE.